PENGARUH BOARD DIVERSITY, INSTITUTIONAL OWNERSHIP, DAN CONSERVATISM TERHADAP EARNING QUALITY - Chavia Zagita, Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of research is to obtain empirical evidence about the impact of board diversity, conservatism, and institutional ownership to earnings quality on manufacture companies listed on the Indonesia Stock Exchange (IDX) in 2016-2018. This study used 30 manufacture companies selected using purposive sampling method for three years. The data used are secondary data in the form of financial statements. The research data was processed using Eviews 10. The result of the research show that board diversity have negative and insignificant effect on earnings quality, conservatism have negative and significant effect on earnings quality, and institutional ownership have positive and insignificant effect on earnings quality. For further research, it is recommended to extending the period of the study and adding other independent variabel.